The Essence of Cryptocurrencies: Descriptive and Comparative Analysis - E. V. Sinel’nikova-Muryleva; K. D. Shilov; A. V. Zubarev (Финансы: теория и практика, 2019)
The aim of the article is to systematize the views on the concept of cryptocurrency from the literature and among international and national organizations and regulators, to analyze its economic essence and the place in the modern monetary and financial system. The definition and the functions of cryptocurrency are discussed in the framework of descriptive and theoretical analysis. The paper systematized the existing approaches to the concept analysis of cryptocurrency; the place of cryptocurrency in modern economic theory is shown.The article concludes that cryptocurrencies are often determined through the set of basic characteristics. Cryptocurrencies are not money, though they can perform the main function of money — to be a means of payment; they can be a means of making settlements, assets, platforms for concluding smart contracts, a means for crowdfunding. They are not private money in Hayek’s interpretation. Cryptocurrencies can be described in the framework of the models of new monetarism (payment economics).